CLUSTERING PROBLEMS IN A MULTIOBJECTIVE FRAMEWORK - YUNAY HERNÁNDEZ (Revista de Matemática: Teoría y Aplicaciones, 2016)
We propose a new algorithm using tabu search to deal with biob jective clustering problems. A cluster is a collection of records tha t are similar to one other and dissimilar to records in other clusters. Cluste ring has appli- cations in VLSI design, protein-protein interaction netwo rks, data mining and many others areas. Clustering problems have been subject o f numer- ous studies; however, most of the work has focused on single-o bjective problems. In the context of multiobjective optimization our ai m is to find a good approximation to the Pareto front and provide a method to make decisions. As an application problem we present the zoning p roblem by allowing the optimization of two objectives.